Auto Tuned Vibration Absorber for Reciprocating Saw: Vibration dynamics modelling, simulation and analysis - Bhagavan, Anjan Nagaiah (My University, 2020)
This thesis work investigates an Auto Tuned Vibration Absorber(ATVA) developed by RISE IVF AB for a reciprocating saw (SR 30-A36). ATVA is a tuned vibration absorber whose stiffness exhibits non-linear behaviour. The project aim was to develop an ATVA prototype for reciprocating saw wherein the system parameters of ATVA are tuned for optimal vibration suppression. The entire work was emphasized on measurement of excitation force, optimization of system parameters, prototype development of ATVA. Prototype development was based on measurements of the excitation force experienced by reciprocating saw while freely running, cutting chipboard and metal-pipe. Actual measurement data was used as input to the simulations and optimization. Further, optimizations were carried out in MATLAB and ADAMS software was used to verify the response obtained. Non-linear stiffness in ATVA is constructed using two linear springs with a gap between them. Earlier, ATVA with a linear spring and gap was used in a prototype and the system had problems getting activated when connected to reciprocating saw. In this thesis work, the main idea to solve the problem of activation was by using an additional spring in the prototype which can activate ATVA as soon as the system gets excited. Optimizations were performed to identify the two spring stiffness required, the gap between them and the auxiliary mass value for optimal vibration attenuation. Finally the activation of ATVA was verified by simulating the operating conditions.
Keywords: Auto Tuned Vibration Absorber (ATVA); Reciprocating saw; non-linear stiffness; linear spring